A study of relationship between social support, work values and job search behavior - Wang, Fang; Qu, Jian-Guo (Frontiers in Psychology, 2022)
The COVID-19 outbreak has put more pressure on the labor market, reducing employment opportunities and increasing graduate unemployment. Therefore, this study was undertaken to explore the relationship between social support, work values and job search behavior. The theoretical model was tested using the data collected from 560 Chinese fresh graduates (Mage = 23.45 years; standard deviation = 2.02). The participants completed questionnaires that assessed their social support, work values and job search behavior. Descriptive statistics and structural equation modeling were used for data analysis. The results indicated that social support was positively and directly associated job search behavior and work value mediated the association between social support and job search behavior. These findings will encourage future researchers to investigate the phenomena of job search behavior.